Micro structure and bonding strength investigation on 3D printed dissimilar materials - Ramesh, Aditya (Nanyang Technological University, 2023)
Multi-metal additive manufacturing via Selective Laser Melting (SLM) is a revolutionary technique that enables the fabrication of complex components with tailored mechanical properties. By selectively fusing metal powders layer by layer, SLM allows for the integration of multiple metals or alloys within a single structure, thus offering unprecedented design freedom and customization possibilities. We have studied how multi-metal additive manufacturing can be used to enhance the life of IN625 valves in petrochemical industries. We have proposed to use SLM technology to selectively clad a more resistant material like CoCrMo on IN625, thereby enabling the fabrication of a valve with a harder surface for wear resistance while maintaining a relatively softer core for improved toughness. The process parameters analysed in this study are laser power, hatch distance, point distance and exposure time. We have emphasized the importance of these process parameters in obtaining a high Vickers hardness number and a high ultimate tensile strength. The optimum process parameters and the best mechanical properties have been observed at a laser power of 250W, hatch distance of 80µm, point distance of 40µm and an exposure time of 80µs. We also found that when the first layer of powder is not remelted, the average interface hardness first increases and then decreases with a decrease in point distance. Moreover, we have concluded that the ultimate tensile strength (UTS) of the samples whose first layer was not remelted is greater than the UTS of the samples whose first layer was remelted thrice. Subsequently, we also found that there was negligible change in UTS of the samples with change in laser power. As research and development efforts continue, multi-metal additive manufacturing via SLM is poised to revolutionize manufacturing processes, open new avenues for innovation and drive advancements in engineering solutions.